Perancangan Permainan Ular Tangga Multiplayer Berbasis Android - Rahmat Hidayatullah; Atma Hadiansa (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2018)
Snake game ladder is a much-loved game on the cellular telephone a few years ago, but as it grew its technology today many people use cell telephone based on android, so snake game that had rucked also lagged. As the game develops in accordance with technology, conventional games that used to be a lot of interest to be left behind. Therefore in this research the ladder snake game will design a game of snake ladder with waterfall method and backtracking algorithm purpose of this research is this game can run on Jellybeans Android OS until latest Android OS version.